PO 61 - ANAESTHETIC MANAGEMENT FOR CAESAREAN IN A PATIENT WITH SYMPTOMATIC CHIARI MALFORMATION – CASE REPORT - Rouxinol Dias, Ana Lídia; Fernandes, Mariana; Oliveira, Flávia; Sampaio, Catarina; Guerra, Marta (Journal of the Portuguese Society of Anesthesiology, 2023)
x